Estudo sobre gestão da manutenção das estruturas de ciclomobilidade na cidade de São Paulo - Silva, Mário Augusto Paixão da (2023)
The city of São Paulo has the largest bicycle network in the country and should remain in the leadership position as the City Hall's Plan of Goals intends to reach the mark of 1.800 kilometers of bicycle mobility infrastructure by 2028. But, paradoxically, the largest bicycle network in the country does not have a management and maintenance system that ensures good conditions of use for cyclists. Currently, the maintenance of RCs is done centrally and without defined resources for this purpose. As a result, the municipality cannot service all the bike lanes and lanes that need maintenance. This repressed demand causes cyclists in São Paulo to assess the maintenance system for cycle lanes and bike lanes as deficient and consider that there is a lack of involvement of the public authorities in solving the problem. Thus, this work proposes alternatives for financing the maintenance of RC's through a linkage of resources from the budget of the Municipal Department of Mobility and Transit (SMT), including the use of funds from the Urban Development Fund (Fundurb) and the Municipal Fund of Transit Development (FMDT). In addition, it proposes to sign the Terms of Cooperation under the Clean City Law, so that companies or individuals assume responsibility for maintaining bicycle infrastructure, creating a collaborative network based on public sector relations with the private sector and civil society as a whole. From the deficiencies identified in the maintenance of the largest bicycle network in Brazil, the research identified the need to develop an application to enable the participation of users in identifying emerging problems in bicycle lanes and lanes and, with this, improved the public policy for bicycle mobility.